Youth substance abuse : a reference handbook - Newton, David E. (Santa Barbara, California : ABC-CLIO, An Imprint of ABC-CLIO, LLC, 2016)
"Youth substance abuse: a reference handbook provides an overview of the history and development of youth substance abuse along with a discussion of the medical, social, psychological, legal, and economic issues associated with youth substance abuse both in the United States and other parts of the world. The book begins with a comprehensive introduction to the subject of youth substance abuse that explains how modern societies have reached the point where abuse of both legal and illegal substances is a major health issue in many nations. Readers will learn about the effects of substances such as cocaine, marijuana, and heroin as well as substances that are typically legal but have deleterious health, social, or psychological effects, such as tobacco, alcohol, prescription drugs, and electronic cigarettes. Subsequent chapters address how and why youth substance abuse has become a problem in the United States and other countries, the demographics of this widespread problem, the direct and indirect effects of youth substance abuse and addiction, and the range of services and methods that are available for treating substance abuse"--Publisher's website.
Background and history -- Problems, issues, and solutions -- Perspectives -- Profiles -- Data and documents -- Annotated bibliography -- Chronology.
Includes bibliographical references (pages 263-303) and index.
Keywords: Youth -- Substance use; Substance abuse